Operational Efficiency of BTPN Syariah During the Covid-19 Pandemic: A Data Envelopment Analysis Approach - Radithya Dzaky Waradana (Islamic Economics and finance in Focus, 2026)
This study analyzes the operational efficiency of BTPN Syariah (2019-2023), a bank focusing on the productive low-income women segment. Amidst the COVID-19 pandemic, the bank faced a "vulnerability paradox" between its shock-prone ultra-micro customer profile and its resilient Sharia business model. Using a two-stage quantitative approach, this study applies Data Envelopment Analysis (DEA) to measure technical efficiency and Tobit Regression to identify its determinants. The DEA results indicate a "U-shaped" efficiency pattern: optimal efficiency was achieved in 2019, contracted in 2020-2021 due to mobility restrictions, and fully recovered in 2023. The Tobit analysis reveals that Bank Size and the BI-Rate have a significant positive effect, confirming the effectiveness of economies of scale and monetary policy adaptation. Conversely, Non-Performing Financing (NPF) and inflation exhibit a significant negative effect due to deteriorating asset quality and declining customer purchasing power, whereas CAR and economic growth show no significant impact. In conclusion, economies of scale and monetary adaptation are the primary drivers of efficiency, while strict control over non-performing financing and the mitigation of inflation risks serve as absolute prerequisites for post-crisis operational sustainability.